Pengaruh Motivasi Terhadap Prestasi Kerja Karyawan Di Daima Hotel padang - Redamasari Redamasari; Yuliana Yuliana (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2020)
1This1research originated from the Industrial Field Experience at Daima Hotel Padang. The author found problems, related to employee work performance and lack of work motivation. This study aims to analyze the effect of work motivation on work performance in Daima Hotel Padang. This1type1of1research1is1quantitative1with a1causal assosiative approach. The population in this study were employees of Daima Hotel Padang. The sample in this study used a purposive sampling technique with a total sample of 46 people, namely employees who already had work performance assessments. Data analysis techniques using data description and simple linear regression test using the SPSS Computer1Program1version116.00. Research results show that: Work motivation is in the good category (52.17%), Job Performance is in the quite good category (58.69%) and the simple linear regression test results obtained R Square value of 0.118. Meaning that motivation significantly influences work performance employees at 11.8% and 88.2% are influenced by other factors.